Pediatric Diabetic Ketoacidosis (PDKA) among newly diagnosed diabetic patients at Dilla University Hospital, Dilla, Ethiopia: Prevalence and predictors - Dinberu Oyamo Oromo (PLoS ONE, 2025)
Background Diabetic ketoacidosis (DKA) is a morbid complication of Type 1 diabetes mellitus(T1DM), and its occurrence at diagnosis has rarely been studied in Ethiopia, despite the many cases seen in the pediatric population. Objective The aim of this study was to know the prevalence of DKA among patients with newly diagnosed diabetes mellitus and identify avoidable risk factors. Method This institution-based retrospective cross-sectional study was conducted from December 1, 2018 to December1, 2022. Newly diagnosed T1DM under 15 years were included in the study. DKA and the new diagnosis of type 1 DM were defined based on the 2022 ISPAD and other international guidelines. A data collection form was used to collect sociodemographic and clinical data. Descriptive, bivariate, and multivariate logistic regression analyses were conducted to identify the risk factors. Result Among the 61 newly diagnosed T1DM pediatric patients admitted, DKA was the initial presentation in 37 patients, accounting for 60.7% of the cases. The mean age at diagnosis was 8 (±3.85) years, with females being more affected. Clinical presentation revealed vomiting accompanied by signs of dehydration (32.4%), with polyuria, polydipsia and weight loss (26.2%) being the most common symptoms. The presence of adequate knowledge of signs and symptoms of DM (AOR = 0.07, 95%CI 0.019–0.0897, P value 0.017) and a family history of DM (AOR = 0.129 95%CI 0.019–0.897, P value 0.039) were protective factors against DKA as the initial diagnosis of DM. Moreover, new-onset type 1 DM without DKA was 1.5 times higher in children from families with a high monthly income (AOR = 1.473, 95% CI 0.679–3.195 p value 0.000) compared to those from families with low income. The presence of an infection prior to DKA (AOR = 11.69,95%CI 1.34–10.1,P value 0.026) was associated with the diagnosis of DKA at the initial presentation of DM. Conclusion A high number of children present with diabetic ketoacidosis (DKA) at the initial diagnosis of diabetes mellitus (DM), which is associated with inadequate knowledge of the signs and symptoms of DM as well as the masking effect of concomitant infections in these children. Healthcare professionals should endeavor to suspect and screen children. Continuous awareness creation of DM is encouraged to diagnose diabetes mellitus earlier and to decrease the prevalence of DKA as an initial presentation.